The Research Context and Hotspots Analysis of WoS and CSSCI of Chemistry Education - Visual Knowledge Graph Analysis Based on CiteSpace - Aorigele,; Narantsogt, Natsagdorj (Lavai - International Journal of Education, 2022)
By collecting the literature related to the Chemistry Education from the Web of Science (WoS) and Chinese Social Sciences Citation Index (CSSCI) from 2000 to 2020, we used the CiteSpace bibliometric method to conduct inductive statistical analysis using the characteristics of age, author, country, research hotspot, and evolution trend. Our results revealed a significant growth trend of literature related to this field after 2009, but a stable core author group had not yet been formed. Our data also showed a lack of sufficient collaborative research among various groups. In this research field, the United States had the largest influence, followed by Germany and Australia. The trending literature was mainly focused on formal studies on the integration of Information Technology and Chemistry in courses, the interdisciplinary research on advanced chemistry courses, the reasons for the difficulties in students' understanding of chemical concepts and their solutions to approaching research, and models and modeling in addition to other subjects. Together, considering our results combined with the analysis of the literature citations, we further clarified the research progress and the current stage of Chemistry Education development. WoS ба CSSCI дээр үндэслэсэн химийн боловсролын судалгааны контекст, халуун цэгийг CiteSpace оюуны зураглал дээр суурилсан дүн шинжилгээ хийх Хураангуй: 2000-2020 он хүртэл WoS (Web of Science) болон CSSCI (Chinese Social Sciences Citation Index)-д багтсан химийн боловсролтой холбоотой өгүүллүүдийг судалгааны объект болгон авч CiteSpace библиометрийн аргыг ашиглан он, зохиогч, улс, судалгааны агуулга, өөрчлөлт шинэчлэлийн чиг хандлага зэрэгт индуктив статистик шинжилгээ хийсэн. Үр дүнгээс харахад 2009 оноос хойш холбогдох судалгааны өгүүллүүд нь мэдэгдэхүйц өсөх хандлагатай байгаа ч одоогийн байдлаар тогтвортой, гол зохиогчийн бүлэг бүрдээгүй, янз бүрийн бүлгүүдийн дунд хамтарсан судалгаа харьцангуй бага байна. Энэ судалгааны салбарт АНУ-ын судлаачдын судалгаа хамгийн их, Герман, Австрали удаалж байна. Судалгааны гол чухал цэг нь мэдээллийн технологи болон химийн хичээлүүдийн уялдаа холбоог судлах, дээд боловсрол дахь химийн хичээлийн салбар дамнасан судалгаа, ЕБС-ийн сурагчдын химийн хэл, ухагдахууныг ойлгоход тулгарч буй бэрхшээлийн шалтгаан, тэдгээрийг шийдвэрлэх арга замын судалгаа, загвар загварчлал зэрэгт төвлөрч байна. Эдгээр үр дүнд суурилсан хавсарсан эшлэлийн судалгааг нэгтгэж, химийн боловсролын судалгааны явц, өнөөгийн хөгжлийн үе шатыг онцолсон болно. Түлхүүр үг: Химийн боловсрол, CiteSpace, Судалгааны халуун цэг, Түлхүүр үгийн дүн шинжилгээ, Чиг хандлага